The Reasons for Primary Tooth Extraction in Primary School-age Children in RSGM Baiturrahmah - Sri Pandu Utami; Deby Anzules; Hamdy Lisfrizal (Denta Journal Kedokteran Gigi, 2021)
Background: Tooth extraction is an important measure in determining oral health status because it generally reflects untreated periodontal tissue disease and caries. Tooth extraction can also be used as a measure of people's knowledge and motivation in maintaining their teeth. The higher the revocation rate, the lower the community's knowledge and motivation. Purpose: The aim of this study is to see the main reasons for tooth extraction in children who are in the pedodontics of the RSGM Baiturrahmah. Material and Methods: This type of research is quantitative with analytic descriptive methods. The target population of this study were students of coass Lab Paedodonti RSGM Baiturrahmah in October-December 2019, with a sample of 76 people. The research was conducted at the Paedodonti Lab RSGM Baiturrahmah in October-December 2019 using a questionnaire. Data analysis using SPSS program with chi square analysis. Results: The distribution of reasons for deciduous tooth extraction is presented, it is found that most of the reasons for extracting deciduous teeth in primary school children are physiological mobility, as many as 53 people (69.7%). In addition, there were 19 people (25%) of the reasons for removal because of excessive retention of 1 person (1.3%), and because of the request of patients / parents as many as 3 people (3.9%). Conclusion: The main reason for the extraction of deciduous teeth in elementary school children at the Lab Paedodonti RSGM Baiturrahmah, was physiological mobility, with the teeth that were often extracted were the mandibular incisors in the 7 year age group.